Association of HIV status with sexual function in women aged 45–60 in England: results from two national surveys. Issue 3 (3rd March 2020) - Toorabally, Nasreen; Mercer, Catherine H.; Mitchell, Kirstin R.; Blell, Mwenza; Burns, Fiona; Gilson, Richard; McGregor-Read, Janine; Allan, Sris; De Ruiter, Annemiek; Dhairyawan, Rageshri; Fox, Julie; Gilleece, Yvonne; et al.
ABSTRACT: Increasing numbers of women living with HIV are reaching their midlife. We explore the association of HIV status with sexual function (SF) in women aged 45–60 using two national cross-sectional surveys: the third British National Survey of Sexual Attitudes and Lifestyles ("Natsal-3") and "PRIME", a survey of women living with HIV attending HIV clinics across England. Both studies asked the same questions about SF that take account not only sexual difficulties but also the relationship context and overall level of satisfaction, which collectively allowed an overall SF score to be derived. We undertook analyses of sexually-active women aged 45–60 from Natsal-3 ( N = 1228, presumed HIV-negative given the low estimated prevalence of HIV in Britain) and PRIME ( N = 386 women living with HIV). Women living with HIV were compared to Natsal-3 participants using multivariable logistic regression (adjusting for key confounders identified a priori : ethnicity, ongoing relationship status, depression and number of chronic conditions) and propensity scoring. Relative to Natsal-3 participants, women living with HIV were more likely to: have low overall SF (adjusted odds ratio (AOR) 3.75 [2.15–6.56]), report ≥1 sexual problem(s) lasting ≥3 months (AOR 2.44 [1.49–4.00]), and report almost all 8 sexual problems asked about (AORs all ≥2.30). The association between HIV status and low SF remained statistically significant when using propensity scoring (AOR 2.43 [1.68–3.51]). Among women living with HIV (only), low SF was more common in those who were postmenopausal vs. Premenopausal (55.6% vs. 40.4%). This study suggests a negative association between HIV status and sexual function in women aged 45–60. We recommend routine assessment of SF in women living with HIV.